The Government's Strategic Role in Marketing Songkok Recca as a Creative Tourism Industry in Bone Regency - A.Bakty, Andi Fatimah Maoudy; Kaddi, Sitti Murni; Badollahi, Muh. Zainuddin; Rahmat, Marfi (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Songkok Recca, a typical cultural product from Bone Regency, South Sulawesi, has great potential in the creative tourism industry. This product not only has historical and symbolic value for the Bugis tribe, but also acts as an important economic resource for local craftsmen, especially in Paccing Village, Mare District. Songkok Recca, resulting from creativity and specialized skills, offers significant economic opportunities for the local community. The government's role in the development and promotion of Songkok Recca is very crucial. The Bone Regency Government has been active in providing guidance and training to craftsmen, as well as promoting this product through various media. Effective public relations and publicity strategies have helped increase recognition and appreciation of Songkok Recca, both at national and international levels. The government is also responsible for maintaining relations with related parties to ensure the continuity and development of this product. Through continued support and a structured marketing strategy, Songkok Recca can continue to develop as a superior regional product that not only strengthens the cultural identity of the Bone community but also makes a significant contribution to the local economy and cultural preservation. This research highlights the importance of synergy between the government and craftsmen in optimizing the potential of Songkok Recca as a main attraction in the creative tourism industry in South Sulawesi.